Reduplication of The Language Tontemboan (Novateur Publications, 2023)
Praise be to the presence of Allah swt. because it wasHis blessing that the author was able to complete thebook entitled Reduplication of the Tontemboan language.In making this book, of course, we as writers were helpeda lot by informants. Through informants, the authorobtained the data needed for analysis. To obtain accuratedata, the author chose informants who mastered theTontemboan language so that all the required data couldbe obtained as expected.The author chose the Tontemboan language to see itsword repetition system because the Tontemboan languagehas many unique features. Therefore, the author feels veryinterested in discussing the Tontemboan languagerepetition system with the hope that the presence of thisbook will provide scientific insight, especially in the field oflanguage, to its readers.In the preparation of this book, of course manyparties helped until it was finished. Therefore, the authorwould like to thank him for his participation in thepreparation of this book. Our hope, as authors, is that thepresence of this book will be useful for its readers.